Direct metal writing and precise positioning of gold nanoparticles within microfluidic channels for SERS sensing of gaseous analytes - Lee, Mian Rong (2020)
We demonstrate a one-step precise direct metal writing of well-defined and densely packed gold nanoparticle (AuNP) patterns with tunable physical and optical properties. We achieve this by using two-photon lithography on a Au precursor comprising poly(vinylpyrrolidone) (PVP) and ethylene glycol (EG), where EG promotes higher reduction rates of Au(III) salt via polyol reduction. Hence, clusters of monodisperse AuNP are generated along raster scanning of the laser, forming high-particle-density, well-defined structures. By varying the PVP concentration, we tune the AuNP size from 27.3 to 65.0 nm and the density from 172 to 965 particles/μm2, corresponding to a surface roughness of 12.9 to 67.1 nm, which is important for surface-based applications such as surface-enhanced Raman scattering (SERS). We find that the microstructures exhibit an SERS enhancement factor of >105 and demonstrate remote writing of well-defined Au microstructures within a microfluidic channel for the SERS detection of gaseous molecules. We showcase in situ SERS monitoring of gaseous 4-methylbenzenethiol and real-time detection of multiple small gaseous species with no specific affinity to Au. This one-step, laser-induced fabrication of AuNP microstructures ignites a plethora of possibilities to position desired patterns directly onto or within most surfaces for the future creation of multifunctional lab-on-a-chip devices.